PENGGUNAAN BUKU DIGITAL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS XII IPS 3 SMAN PAKUSARI JEMBER (Studi Kasus Pada Mata Pelajaran Ekonomi Materi Jurnal Penyesuaian Pada Perusahaan Dagang Semester Genap Tahun Ajaran 2019/2020) - Tiara Tiara; Fergi Diarta; Sri Kantun (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2021)
This research aims to improve motivation and study 12 social 3’s students in SMAN Pakusari Jember by using the digital book. This research is action research that has done in 2 cycles. The first cycle uses the cooperative learning method, and the result showed that students' motivation score was 3,4, which belonged to the medium category. The study results on the first cycle; students had 81 of the average score with a classical standard up to 78,1%. In the second cycle, the strategy applied was a drill, which resulted in a score of 4.5 in the higher category. The mean of students’ learning result increased up to 88% and the classical standard 96.8%. For the next research, the researcher hoped that the researcher could use a digital book with the complete features and material than in this research.